Modeling Transfer Learning for Efficient Code Reuse in Large-Scale Software Development (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The important issues of code reuse in contemporary software development are covered in this study. Reusing code is an essential technique that raises software quality, lowers development costs, and increases productivity. However, because of problems like code repetition, a lack of knowledge of reusable components, maintenance difficulties, and scalability constraints, traditional approaches like libraries, APIs, and design patterns frequently fail in large-scale software development. Especially in big, distributed, and dynamic systems, these difficulties result in inefficiencies, longer development times, and lower software quality. In order to overcome these obstacles, this study suggests using transfer learning, a machine learning method that makes use of pre-trained models to enhance the recognition, modification, and incorporation of reusable code elements. The use of transfer learning in code reuse is a promising way to overcome the drawbacks of conventional approaches, and it has demonstrated notable success in domains such as computer vision and natural language processing. Through the use of models that have already been trained on sizable code corpora (such as open-source repositories like GitHub), transfer learning can help developers find and reuse high-quality code fragments across projects and programming languages more effectively, cutting down on duplication of efforts and enhancing code maintainability. The main aim of this study is to model how to use transfer learning for efficient code reuse in large-scale software development. Using extensive code datasets from private codebases or open-source repositories (like GitHub and GitLab), the study employed a quantitative methodology with a population size of 225. The findings show that CodeBERT is both robust and adaptable, offering high value for software engineering automation and developer assistance tools. The results demonstrate that the model whether trained from scratch or through transfer learning achieved perfect performance metrics in classifying and evaluating code snippets. This high accuracy indicates a strong capacity to enhance software development efficiency by enabling faster and more reliable code assessment. The equal performance of the transfer learning approach further shows that pretrained knowledge from large-scale open-source code can be effectively adapted to new tasks without compromising code quality or consistency. Overall, the findings confirm that the transfer learning model is not only stable and effective but also capable of delivering performance comparable to a fully trained model while requiring significantly less training data and computational resources. Use CodeBERT for automated code assessment, early bug detection, and identifying risky code patterns. Embed the model into Continuous Integration/Continuous Deployment (CI/CD) systems to enable automatic code review and error detection. Fine-tune with domain-specific datasets to maintain consistency with organizational coding standards. Conduct workshops to demonstrate efficiency gains from automated code evaluation.